Effects of growth and maturation on talent identification and selection in an elite youth football academy - Hill, M. (University of Bath, 2021)
Talent identification and development pathways are confounded by relative age, adolescent growth, and biological maturation, where chronologically and biologically older players are provided with an advantage. While increases in size and improvements in speed, strength and power are advantageous for youth football players, the growth spurt can also increase injury risk and adversely affect motor coordination. Adolescence therefore presents a unique challenge for youth athletes and their coaches. This thesis investigates how adolescent growth and maturation affects male youth academy football players and their coaches. Both quantitative and qualitative approaches are used to explore how coaches perceive, experience, and evaluate adolescent players. Coaches evaluations of players' match performances were significantly predicted by biological age in some age groups, where advanced maturity predicted a higher grade; however, chronological age did not significantly predict coaches match grades (study one). The adolescent growth spurt also influenced coaches' evaluations of performance, with grades declining from pre- to during- growth spurt, before increasing again postgrowth spurt (study two). These findings were advanced further by a mixed-methods longitudinal design, tracking adolescent boys and their respective coaches for 12 months to understand how coaches experience, perceive and manage growing and developing adolescent players (study three). Coaches perceived and described the adolescent growth spurt as problematic, with many players described as struggling with various signs and symptoms. Perceptions and expectations of players also differed by biological maturity status, where early maturing players were portrayed as physically dominant and provided greater opportunities for teams to win games, thus, coaches expectations were greater. Later maturing players, although technically and tactically advanced, had little impact on matches, thus, coaches explained it was harder for later maturing players to remain within the system. Finally, the competitive nature of the academy system further exacerbated the implications of adolescent growth and maturation within youth football; the importance of winning games influenced coaches' evaluations, game time, and selection opportunities. The complexity of managing adolescent athletes was highlighted within this thesis. Further research and education within talent pathways are required to reduce biases associated with individual differences in biological maturity and the growth spurt.